CHEMICAL COMPOSITION OF LEATHER USED FOR TRANSFORMATION ASSORTMENT AND RESEARCH OF PHYSICAL-MECHANICAL PROPERTIES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The purpose of this scientific research is to select the type of leather used for the transformation assortment and to select a durable leather for the transformation assortment based on the study of the physical and chemical properties of the selected finished leather.